URDU:BASIC RULES AND REGULATIONS PROHIBITING TRADE (RESEARCH STUDY IN THE CONTEXT OF SHARIA LAW) - Shahzada Imran Ayub (دی اسکالر, 2021)
Trade and commerce are an integral part of human life; therefore, it is important to know its Islāmic principles and laws. Because in matters (business and transactions, etc.) the principle is that everything is ḥalāl unless there is evidence of its prohibition. Therefore, if the rules that make a business fall into the category of ḥāraām are known, so halal sources of income can be easily adopted according to the Shariāh requirements. Considering the Shari'ah arguments and the sayings of the Islamic Scholars and Jurists, the result of the rules and regulations that prohibit any trade is that it is haraam to trade in anything that is forbidden by sharee'ah, it is haraam to trade in anything that is najis (impure) or ḥāraām, It is ḥāraām to trade in anything that is a source of sin, any trade involving fraud, dissatisfaction of the parties, loss of seller or customer, unknown saleable item or unknown price is ḥāraām, trade is haraam in times or places where trade is forbidden such as after the call to prayer on Friday and buying and selling in mosques, etc. It is ḥāraām to trade in anything that is intoxicating and any trade that involves interest in any way is haraam.